1979
DOI: 10.1073/pnas.76.3.1519
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for selection by male mating success in natural populations of Drosophila pseudoobscura.

Abstract: Gene arrangement frequencies were determined at two stages in the life history of Drosophila pseudoobscura taken from nature. Three po ulations in the central highlands of Mexico were each sampled twice during 1976.Gene arrangement frequencies were measured in adult males and in larvae that were the offspring of females collected at the same time. The adult males were in all likelihood a representative sample of those who fathered the larvae produced by the wild females. Differences in gene arrangement frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 25 publications
1
43
2
Order By: Relevance
“…Male reproductive fitness in Drosophila has also been seen to have substantial genetic variation compared to several other components of fitness (Prout, 1971 ;Anderson et al, 1979 ;Brittnacher, 1981 ;Kosuda, 1983 ;Miller & Hedrick, 1993 ;Hughes, 1995). In two of these studies, the genotypes screened were either morphological mutants (Prout, 1971) or karyotypes (Anderson et al, 1979), which in both cases were known to be associated with major fitness effects, making a direct comparison with our populations difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male reproductive fitness in Drosophila has also been seen to have substantial genetic variation compared to several other components of fitness (Prout, 1971 ;Anderson et al, 1979 ;Brittnacher, 1981 ;Kosuda, 1983 ;Miller & Hedrick, 1993 ;Hughes, 1995). In two of these studies, the genotypes screened were either morphological mutants (Prout, 1971) or karyotypes (Anderson et al, 1979), which in both cases were known to be associated with major fitness effects, making a direct comparison with our populations difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In two of these studies, the genotypes screened were either morphological mutants (Prout, 1971) or karyotypes (Anderson et al, 1979), which in both cases were known to be associated with major fitness effects, making a direct comparison with our populations difficult. In the other four studies, lines rendered homozygous for entire chromosomes were shown to undergo inbreeding depression for various measures of male mating success (Brittnacher, 1981 ;Kosuda, 1983 ;Miller & Hedrick, 1993 ;Hughes, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…+ heterozygote is detected in cages of low modifier background (averages of fertility estimates were 0.63 and 0.44 in cages L1 and L2, respectively). This is not an unusual result because there are many cases in the literature where fertility selection is an important component of total selection (Polivanov & Anderson, 1969;Sved & Ayala, 1970;Sved, 1971;Bundgaard & Christiansen, 1972;Anderson et al, 1979). On the other hand, our experimental design for fitness estimation splits total fitness into a component of preadult survival or egg-to-adult viability and into an adult fitness component or fertility.…”
Section: Discussionmentioning
confidence: 98%
“…The concept of partitioning the action of natural selection into several fitness components has been an important one in stimulating well-designed experiments demonstrating the significance and relative importance of the various components of natural selection. Contrary to the traditional belief about the action of natural selection was the evidence that the adult male component, instead of viabilities of zygotes, played a decisive role in the genetic make-up of different Drosophila populations (Prout, 1971a, b;Bundgaard and Christiansen, 1972;Anderson et a!., 1979;Brittnacher, 1981). In addition, there is also extensive evidence that sexual selection is an important component in the dynamics of polymorphisms (Anderson and Watanabe, 1974;Anderson and McGuire, 1978;Fontdevila and Méndez, 1979;Anderson and Brown, 1984).…”
Section: Introductionmentioning
confidence: 93%